AKTIVITAS RASULULLAH SEBAGAI PENDIDIK - Juaidi Arsyad (Universitas Islam Negeri Sumatera Utara, 2016)
As an educator, Rasulullah (pbuh) succeeded in building communities of societies most barbaric be the most civilized society, of an ignorant society into a society which is educated. During thirteen years in Mecca and ten years in Medina, he has managed to become a successful educator who later gave birth to many characters the message of God’s future generations. They are students of upbringing of the Prophet. In the view as teachers, educators enrich themselves is very important in developing a professional attitude as a teacher by ensuring that data and information about the activities of the Prophet as an educator. By studying the Prophet’s educational activity is expected educators undergo more spirit professionalism and hopefully be able to emulate and imitate his every move as being an exemplary teachers.Keywords:Activities, Education